Oxigenoterapia en paciente masculino de 60 años con fibrosis pulmonar idiopática. - Tómala Macías, Narcisa Belén (2020)
Pulmonary fibrosis is a lung disease that occurs when lung tissue is damaged and scarring occurs. This thickened and stiff tissue makes it harder for your lungs to function properly. As pulmonary fibrosis worsens, you have more and more difficulty breathing. Scar formation related to pulmonary fibrosis can be due to a number of factors. Without ban, in most cases, doctors cannot individualize the cause of the problem. When no cause can be found, the condition is called idiopathic pulmonary fibrosis. Damage to the lungs caused by pulmonary fibrosis cannot be repaired, but medications and therapies can sometimes help relieve symptoms and improve quality of life. For some people, a lung transplant may be appropriate.